A Rare Case of Single-Rooted Mandibular Second Molar with Single Canal - Abdulmohsen Alfadley; Ahmad Alquraishi; Yaser Almazrou; Fahd Aljarbou (Case Reports in Dentistry)
The root canal anatomy of mandibular second molar teeth is known to be highly variable. Whilst the most frequently seen configuration is two mesial canals and one distal canal, other variations such as four canals, two canals, and C-shaped canal system do also exist. This case report describes the diagnosis and management of unusual root canal configuration of a mandibular second molar, with one canal in a single conical root, using the contemporary advancements in endodontics. Following clinical and radiographic examinations of the case, a diagnosis of symptomatic irreversible pulpitis with symptomatic apical periodontitis of tooth #47 was established, and root canal treatment followed by composite buildup and crown were planned. Clinicians should be aware of the different anatomic variants each tooth may exhibit. Furthermore, clinicians need to possess the proper knowledge and skills that allow them to utilize the diagnostic and therapeutic tools available at their disposal in order to optimize the quality of care provided to their patients.